How the Brain Learns Best. - HORVATH, JARED COONEY (Psychology Today)
The article discusses the findings of research consolidated by neuroscientists exploring human condition about how the brain best takes information. Topics include the role of empathy in learning, the importance of having the opportunity to exercise higher-order cognitive skills like critical thinking and creativity, and the best way to conceive of human attention.